Control Contestability, Large Shareholder Identity, and Corporate Risk-Taking: International Evidence - Cid-Aranda, C (Elsevier B.V., 2025)
We analyse the relationship between ownership structure and corporate risk-taking in a sample of 271 listed firms from Brazil, Chile, Colombia, Mexico, and Peru between 2005 and 2020. We find that contesting the largest shareholder increases corporate risk-taking. We also show that the influence of largest shareholders on corporate risk-taking is conditional on shareholder identity; whereas family and government control is associated with lower corporate risk-taking, foreign control has the opposite influence. Finally, our results show that when the two largest shareholders are families, they align their interests to support conservative decisions and that when the largest shareholder is a family but the second is an institutional investor, contesting control attenuates suboptimal risk policies. Our results contribute to the literature by reporting evidence to disentangle the heterogeneity within blockholders and the bivalent relationship between controlling and non-controlling large owners. We provide valuable results to policymakers, investors, and practitioners alike vis-à-vis discussing how specific ownership structures encourage risk-taking attitudes and –presumably– value-increasing policies. © 2024 Board of Trustees of the University of Illinois